Investigation of Dynamic Characteristics of Vibrating Components and Structure Through Vibration Measurement and Operational Modal Analysis - Amirza, Mohammad Aarif; Anuar, Muhamad Azhan; Azhar, Anis Shafiqah; Shaarani, Noor Mohamad; Abdul Rahman, Zamri; Mohd Anuar, Mohd Afzan (International Journal of Integrated Engineering, 2023)
Smooth plant production is utmost expected by plant owners since any unplanned shutdown is very much undesirable as it may incur loss of company’s profits and other repercussions. Critical operational assets such as rotating machineries and their components, e.g., motor, pump, compressor, and turbines are crucial to be monitored in ensuring continuous operation of the plant. Therefore, vibration being one of the elements in predictive maintenance is much needed. This paper addresses the monitoring and findings for predictive maintenance on high vibration of a make-up gas compressor in one of the oil & gas and petrochemical plant in Malaysia. The conventional vibration measurement using vibration analyzer was utilized to identify the severity of the machine vibrations through the overall vibration value obtained on the motor and compressor. A specialized vibration measurement technique, namely, Operational Modal Analysis (OMA) was further deployed to verify the presence of resonance on the equipment by obtaining its dynamic characteristics, i.e., natural frequency and mode shape. The findings showed clear indication of resonance occurrence as similar frequency (112 Hz) was identified from both vibration measurement and operational modal analysis.